Psychological Flexibility and Its Relationship to Distress and Work Engagement Among Intensive Care Medical Staff - Holmberg, Johan; Kemani, Mike K.; Holmström, Linda; Öst, Lars-Göran; Wicksell, Rikard K. (Frontiers in Psychology, 2020)
Intensive care settings place specific work-related demands on health care professionals that may elicit stress and negatively influence occupational health and work engagement. Psychological flexibility has emerged as a promising construct that could help explain variation in reported health. Understanding the role of psychological flexibility in occupational psychological health among intensive care medical staff may potentially guide the development of effective interventions. Thus, the present study evaluated the relationships between psychological flexibility (Work-related Acceptance and Action Questionnaire), distress (Perceived Stress Scale, General Health Questionnaire) and work engagement (Utrecht Work Engagement Scale) in a sample of 144 health care professionals from one adult (ICU, N=98) and one pediatric (PICU, N=46) intensive care unit. In addition to cross-sectional analyses, a subset of data (PICU, N=46) was analyzed using a longitudinal design. Results illustrated that higher levels of distress were associated with lower levels of work engagement. Furthermore, psychological flexibility was related to greater work engagement, and psychological flexibility had a significant indirect effect on the relationship between distress and work engagement. Lastly, increased psychological flexibility over time corresponded with increased work engagement. Although tentative, the results suggest the importance of psychological flexibility for work engagement in health care professionals within intensive care settings.